196k views
4 votes
I need help please
Thanks

I need help please Thanks-example-1
User Mechaadi
by
5.0k points

1 Answer

1 vote

Answer:


the \: formulea \: is \: : \\ y = \frac{20x {}^(3) }{ {h}^(2) }


x = \sqrt[3]{\frac{yh {}^(2) }{20} } = \sqrt[3]{\frac{67.5h * h {}^(2) }{20} } = (3h)/(2)

Explanation:


y \: \alpha \: x {}^(3) \\ y = kx^(3) \\ k = \frac{y}{x {}^(3) } =\frac{20h}{x {}^(3) } = \frac{20h}{h {}^(3) } = \frac{20}{h {}^(2) } \\ \\ when \: y \: = 67.5h \: then \\ x = \sqrt[3]{ (k)/(y) } = (3h)/(2)

User Rohitpaniker
by
4.7k points